Influence of different extraction techniques on the chemical profile and biological properties of Anthemis cotula L.: Multifunctional aspects for potential pharmaceutical applications - DOĞAN, AHMET; EMRE, GİZEM; ŞENKARDEŞ, İSMAİL (ELSEVIER SCIENCE BV, 2019)
The phytochemical composition of different extracts obtained from stinking chamomile (Anthemis cotula L) was investigated. Ethanol was used as solvent and accelerated solvent extraction (ASE), microwave assisted extraction (MAE), maceration, soxhlet extraction (SE), and ultrasound assisted extraction (UAE) were applied on plant material. Comparison of the phytochemical contents, antioxidant, and enzyme inhibitory properties were performed. The most abundant sesquiterpene in the extracts was anthecotuloide, while the most present phenolics were caffeoyl quinic acid, quercetin, and kaempferol derivatives. UAE extract was the most efficient in the extraction of sesquiterpenoids and polyphenols. Considering the assays on antioxidant activity and enzyme inhibition, ASE extract showed highest phenolic content (62.92 mg gallic acid equivalent/g extract). Likewise, this extract showed highest radical scavenging (103.44 mg trolox equivalent [TE]/g extract and 155.70 mg TE/g extract, for DPPH and ABTS assays respectively) and reducing power potential (435.32 and 317.89 mg TE/g extract, for CUPRAC and FRAP assays, respectively). The different extracts showed similar results in the enzyme inhibition assays suggesting that the extraction methods used have no effect on observed enzyme activities. Novelty of our findings are the inhibitory action of the ethanol extract of A. cotula aerial parts on key enzymes associated with Alzheimer's disease (acetyl cholinesterase, butyryl cholinesterase), type 2 diabetes (alpha-amylase, alpha-glucosidase), and skin hyperpigmentation disorders (tyrosinase). Data collected from the present work further appraises the multiple potential biological properties of stinking chamomile suggesting the need for further investigation on its constituents. (C) 2019 Elsevier B.V. All rights reserved.
Keywords: Anthemis cotula; H-1-NMR; Anthecotuloide; Sesquiterpenoids; Antioxidant; Enzyme inhibitor; SESQUITERPENE LACTONES; ANTIOXIDANT; ASTERACEAE; BIOACTIVITY